1995
DOI: 10.1002/cne.903520102
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and development of β‐adrenergic receptors in the rat olfactory bulb

Abstract: Beta-adrenergic stimulation appears to be involved in the establishment of both learned olfactory preferences and functional changes in the olfactory bulb of young rats. We examined the postnatal development of beta-adrenergic receptors within the main olfactory bulb to determine the density and distribution of these receptors. To quantify beta-adrenergic receptor density, olfactory bulb homogenates from postnatal day (PND) 1, 6, 12, and 19 rats were assessed for receptor binding with 125I-iodopindolol. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…Both papers indicated weak localization of ␤ 1 -adrenoceptors (in situ hybridization, Nicholas et al 1993) or ␤-adrenoceptors (immunocytochemistry, Wanaka et al 1989) in the granule cell layer of the bulb as also is seen in a small subset of cells in the present study. A developmental binding study targeted to the olfactory bulb further indicated that most ␤ 1 -adrenoceptor binding occurred in layers other than the mitral cell layer and increased developmentally (Woo and Leon 1995). In a later study the same investigators reported that locus coeruleus lesions increased ␤-adrenoceptor density in the glomerular layer (Woo et al 1996), suggesting that this region might be most responsive to locus coeruleus input.…”
Section: Yuan Et Almentioning
confidence: 97%
See 1 more Smart Citation
“…Both papers indicated weak localization of ␤ 1 -adrenoceptors (in situ hybridization, Nicholas et al 1993) or ␤-adrenoceptors (immunocytochemistry, Wanaka et al 1989) in the granule cell layer of the bulb as also is seen in a small subset of cells in the present study. A developmental binding study targeted to the olfactory bulb further indicated that most ␤ 1 -adrenoceptor binding occurred in layers other than the mitral cell layer and increased developmentally (Woo and Leon 1995). In a later study the same investigators reported that locus coeruleus lesions increased ␤-adrenoceptor density in the glomerular layer (Woo et al 1996), suggesting that this region might be most responsive to locus coeruleus input.…”
Section: Yuan Et Almentioning
confidence: 97%
“…As noted by Woo and Leon (1995), because iodopindolol is biased toward the detection of ␤ 2 -adrenoceptors, even examining radiolabeling in the presence of a ␤ 2 -adrenoceptor antagonist may not be sufficient to eliminate some binding of ␤ 2 -adrenoceptors, which are numerous in the olfactory bulb. The profiles of the two receptors seen in the binding studies were identical except for additional external plexiform labeling for ␤ 2 -adrenoceptors.…”
Section: Yuan Et Almentioning
confidence: 99%
“…1). Both ␣ and ␤ adrenergic receptors are expressed by cells in the MOB (Pieribone et al 1994;Woo and Leon 1995;Day et al 1997). Current evidence suggests that the LC-NA system has a behaviorally meaningful role within the MOB of adult animals engaged in olfactory learning tasks.…”
mentioning
confidence: 99%
“…Norepinephrine released by locus coeruleus activation would interact with all adrenoceptor subtypes present in the olfactory bulb. Both ␤1-and ␤2-adrenoceptor subtypes are present in the olfactory bulb (Nicholas et al 1993;Woo and Leon 1995) and would be activated by isoproterenol. ␣-Adrenoceptor subtypes also occur in the olfactory bulb (McCune et al 1993).…”
mentioning
confidence: 99%
“…These groups were tested against the learning effective dose of phenylephrine (1 mg/kg) as well as the usual controls (six litters, 46 pups). This added condition was required because ␣1-adrenoceptors are present in both the locus coeruleus (McCune et al 1993) and olfactory bulb (McCune et al 1993;Pieribone et al 1994), while ␤-adrenoceptors are present in the olfactory bulb (Woo and Leon 1995) but not in the locus coeruleus (Nicholas et al 1993). Thus, blocking the ␤-adrenoceptors in the olfactory bulb, while activating ␣1-adrenoceptors, would rule out ␤-adrenoceptor involvement in learning in the presence of ␣1-adrenoceptor activation.…”
mentioning
confidence: 99%